2008
DOI: 10.1093/rheumatology/ken179
|View full text |Cite
|
Sign up to set email alerts
|

The registry of the German Network for Systemic Scleroderma: frequency of disease subsets and patterns of organ involvement

Abstract: Objective. Systemic sclerosis (SSc) is a rare, heterogeneous disease, which affects different organs and therefore requires interdisciplinary diagnostic and therapeutic management. To improve the detection and follow-up of patients presenting with different disease manifestations, an interdisciplinary registry was founded with contributions from different subspecialties involved in the care of patients with SSc.Methods. A questionnaire was developed to collect a core set of clinical data to determine the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
159
2
24

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(208 citation statements)
references
References 21 publications
(32 reference statements)
23
159
2
24
Order By: Relevance
“…9 On the other hand, Hunzelmann et al reported that renal involvement is twice as common in patients with ssSSc than it is in patients with systemic sclerosis. 10 Additionally, renal insufficiency was also more than twice as common in the patients as compared to the total group of systemic sclerosis patients. An analysis of the literature revealed a relatively high rate of case reports describing patients with renal failure due to systemic sclerosis without or with delayed cutaneous manifestations.…”
Section: Renal Involvementmentioning
confidence: 95%
See 2 more Smart Citations
“…9 On the other hand, Hunzelmann et al reported that renal involvement is twice as common in patients with ssSSc than it is in patients with systemic sclerosis. 10 Additionally, renal insufficiency was also more than twice as common in the patients as compared to the total group of systemic sclerosis patients. An analysis of the literature revealed a relatively high rate of case reports describing patients with renal failure due to systemic sclerosis without or with delayed cutaneous manifestations.…”
Section: Renal Involvementmentioning
confidence: 95%
“…1.5 and 7.5%, respectively. 8,10 Most of the literature is limited to descriptions of isolated cases, usually containing additional rare features, complications or associated conditions. According to Marangoni et al, the total number of 139 cases was reported until 2012.…”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…ILD, which occurs at a frequency of 34%-60% in patients with SSc (Meyer et al 2007;Hunzelmann et al 2008;Hashimoto et al 2012), is currently the primary cause of SSc-related death (Ioannidis et al 2005;Steen and Medsger 2007). However, no agents have been proven to effectively control ILD .…”
Section: Introductionmentioning
confidence: 99%
“…Scleroderma is an autoimmune disease characterized with fibrosis (1-2).Clinically, systemic sclerosis is a heterogeneous disease with different sub-groups characterized by visceral involvement, measured by the presence of different antibodies (3,4). It is a rare disease with a prevalence ranging from 50 to 300 in a million.…”
Section: Sclerodermamentioning
confidence: 99%